Renormalization Group and 3-3-1 Model with the DiscreteFlavour Symmetries - Long, Hoang Ngoc; Ngan, Nguyen Thi Kim (Communications in Physics, 2012)
Renormalization group equations of the 3-3-1 models with A4 and S4 flavor symmetries as the only intermediate gauge group between the standard model and the scale of unification of the three coupling constants are presented. We shall assume that there is no necessarily a group of grand unification at the scale of convergence of the couplings